(untitled) (University of Warwick Press, 2017)
Everyone wants to be happy. Over the ages, tracts of the ancient moral philosophers – Plato, Aristotle, Confucius – have probed the question of happiness. The stirring words in the preamble to the Declaration of Independence that established ‘Life, Liberty and the pursuit of Happiness’ as ‘unalienable Rights’ served as the inspiration that launched a nation, the United States of America. Yet, more than 240 years later, the relationship between government’s objectives and human happiness is not straightforward, even over the matters of whether it can and should be a government aim. We approach this question not as philosophers, but as social scientists seeking to understand happiness through data. Our work in these pages is intended to enhance understanding of how the well-being of individuals and societies is affected by myriad forces, among them: income, inflation, governance, genes, inflation, inequality, bereavement, biology, aspirations, unemployment, recession, economic growth, life expectancies, infant mortality, war and conflict, family and social networks, and mental and physical health and health care. Our report suggests the ways in which this information might be brought to bear to rethink traditional aims and definitions of socioeconomic progress, and to create a better – and, yes, happier – world. We explain what the data say to us: our times demand new approaches. Foreword by Richard Easterlin; Introduced by Diane Coyle.